Integrated health information systems framework in post natal care for modern and traditional Malay medicine - Raja Ikram, Raja Rina (2017)
The overall aim of this research is to produce an integrated health information systems framework for Traditional Malay Medicine (TMM) and modern medicine in the field of postnatal care. A qualitative study based on grounded theory was conducted via healthcare experts in the field of modern medicine, Traditional Malay Medicine, and information technology (IT) subject matter experts. This research examined health information systems applications in modern and traditional medicine systems, provide an overview of TMM services in Malaysia and critically analyse the existing electronic health records structures and interoperability standards available. A conceptual framework was initially proposed from the literature review and analysis of interviews of the current framework. This research also investigated the critical data attributes required for Traditional Malay Medicine in postnatal care. A set of critical data attributes was developed and proposed from the analysis of results of the structured interviews. An information model was then developed from the set of critical data attributes. A common TMM data attributes in postnatal care may assist in making the proposed framework more flexible and interoperable, particularly when applied with relevant healthcare interoperability standards. The conceptual framework was then validated via healthcare practitioners and IT industry experts. A prototype system of electronic health record was also examined by the respondents to validate the proposed conceptual framework via exploratory prototyping. Consequently, the validation findings was analysed and new themes that emerged from the findings was highlighted to be included in the revised framework. A revised integrated health information systems framework proposed included health record information, interoperability standards, training, support, awareness, separation of authority, accreditation, regulation and enforcement, and adoption incentives. This research may significantly contribute to four main audiences – software developers, healthcare providers, Malay medicine practitioners, and Malay confinement users. Malay women who are the main users of postnatal treatment shall benefit from information availability to compare services delivered by providers. Healthcare providers shall benefit from the standardization of information exchange with other healthcare providers. Software developers may use this study to assist them in developing healthcare related applications in the postnatal domain, particularly in the design of a generic and extensible information model.